A comparative analysis of the Lancaster House Constitution and the new Constitution of Zimbabwe (2013) in the context of human rights protection - Jongwe, Tapfuma Ronald (Midlands State University, 2018)
This study sought to carry out a comparative analysis of the Lancaster House Constitution and the Constitution of Zimbabwe (2013) in the context of human rights protection. Through the gathering and subsequent analysis of data gathered from both primary and secondary sources the research sought to establish the provisions of the 2013 constitution that guarantee human rights protection and also establish the provisions of the Lancaster House Constitution that were a direct violation of human rights and establish how such provisions have been dealt with as provided for by Chapter 4 of the new constitution or any other provisions provided for in the new constitution. The research was mainly qualitative in nature and used interviews and FDGs as the sources of primary data whilst a thorough document analysis was carried out so as to gather secondary data and build a better understanding of the background of the research problem. The research established that the 2103 Constitution is bay far a better off document than the Lancaster House Constitution as it provides for a Declaration of Rights that is binding and enforceable at law. The research also noted that Zimbabwe stands to enjoy a better human rights record under the new supreme law as among other issues it ensures the separation of powers and establishes key institutions and provides for judicial avenues that may be sought in cases were human rights are violated.